PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 125 PEKANBARU - Risky Syahputri; Syahrilfuddin Syahrilfuddin; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research started from the problem of low learning outcomes of mathematics of grade III students in 125 Elementary School in Pekanbaru, which is have an average grade of 65,52 under completeness criteria minimum value (KKM) that is 73. From 23 students, there are only 10 students who achieve the KKM with classical completeness of 43%. This research is the type of Classroom Action Research (CAR) in 2 cycles which the aims is to improve outcomes in mathematics learning of student grade III students in 125 Elementary School in Pekanbaru by Application Pendidikan Matematika Realistik Indonesia (PMRI) approach. The data which are collected in this research are the teachers and students activity and also the learning report. After carrying out teacher activity in the cycle I of the first meeting obtained score of 14 (70%) with sufficient category and at the second meeting obtained score of 15 (75%) with sufficient category. While on the cycle II of the first meeting obtained the score of 17 (85%) with good category and the second meeting obtained score of 18 (90%) with very good category. The increasing of student activity on cycle I of first meeting get score of 13 (65%) with sufficient category and at second meeting get the score of 17 (85%) with good category. While in the cycle II of the first meeting obtained score of 17 (85%) with good category and the second meeting obtained a score of 18 (90%) with very good category. The results obtained by studying the average learning outcome measures 65,52 rising to 71,08 in cycle I with rising percentage 8,48%. In cycle II ricing to 82,39 with rising percentage 25,74%. The result of there search in grade III students in 125 Elementary School in Pekanbaru proves that by Application Pendidikan Matematika Realistik Indonesia (PMRI) approach can improve students' mathematics learning outcomes.Key Word: Pendidikan Matematika Realistik Indonesia (PMRI) approach, MathematicLearning Outcome.